2007
DOI: 10.1002/app.24714
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of cardanol‐grafted natural rubber—The solution technique

Abstract: Cardanol, a by-product of the cashew industry, has been recently proven to be a multifunctional additive (MFA) in rubbers. It is expected that grafting of cardanol onto natural rubber (NR) would impart inherent MFA characteristics to the rubber. Grafting has been carried out in solution using toluene as the solvent and a peroxide initiator. Optimized conditions of grafting reaction could be arrived at using a statistical tool namely orthogonal array testing strategy, keeping the maximum percentage of grafting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 14 publications
(6 reference statements)
0
22
0
Order By: Relevance
“…It includes more than one compound because the composition of the side chain varies in its degree of unsaturation . Cardanol components are 48% mono‐unsaturated, 16% bi‐unsaturated, and 29% tri‐unsaturated which represents 2 average double bonds per chain. Chemical and physical properties of cardanol are very close to those of DEHP.…”
Section: Bio‐based Plasticizersmentioning
confidence: 99%
“…It includes more than one compound because the composition of the side chain varies in its degree of unsaturation . Cardanol components are 48% mono‐unsaturated, 16% bi‐unsaturated, and 29% tri‐unsaturated which represents 2 average double bonds per chain. Chemical and physical properties of cardanol are very close to those of DEHP.…”
Section: Bio‐based Plasticizersmentioning
confidence: 99%
“…It has been reported that cardanol can also be used along with ligninbased compounds for the synthesis of polyurethanes that exhibit good thermal and mechanical properties (Minh Tan, 1996). The unsaturated chains of cardanol have been grafted with natural rubber to increase heat stability and the resulting compounds were reported to exhibit much better thermo-oxidative stability (Vikram and Nando, 2007). Derivatives of cardanol have also shown promise as anti-oxidants in the stabilization of gasoline (Dantas et al, 2003).…”
Section: Cardanolmentioning
confidence: 98%
“…An important attribute of cardanol is that it is a biodegradable monomer and degrades to 96% of its original weight within 28 days (2). Cardanol and its derivatives have been utilized for a variety of applications such as resins (2), friction lining materials (3), and surface coatings (4). Cardanol has been polymerized using oxidative catalysts such as iron salen (5).…”
Section: Introductionmentioning
confidence: 99%